Heat Compress to Reduce Chronic Pain in Hepatoma Patients - Hendri Tamara Yuda; Andika Abdul Malik; Wina Widianti; Nida Siti Padilah (Genius Journal, 2021)
Background: Hepatoma is an abnormal growth of liver cells, which is characterized by a mass in the right upper abdomen, which can cause chronic pain. Pain arises from tissue damage and inflammation of the liver. One of the nursing interventions that can be done to overcome the main problem of chronic pain is hot compresses. Objective: This study aims to present nursing care with hot compress intervention as an effort to overcome the main problem of chronic pain in hepatoma patients. Methods: This case study uses nursing care methods that include assessment, determination of nursing diagnoses, nursing plans, implementation of nursing and nursing evaluation which was carried out for 3 days in the aster room of the Banjar City Hospital. The assessment was carried out by way of history taking and observation. Nursing diagnosis is determined by the IDHS, while the nursing plan is adjusted to the grouping of interventions in SIKI supported by Evidence Based Nursing. Implementation and evaluation of nursing is documented with the SOAPIER model. Giving hot compress therapy to hepatoma patients is given using a bottle covered with a cloth so that the heat does not directly stick to the skin, with a duration of 15 minutes. Results: After being given a heat compress intervention, the pain scale was reduced from 8 to 2, while the subjective data from the anamnesis, the client said the pain was reduced. Conclusion: Heat compress therapy can be an effective nursing intervention to reduce chronic pain in hepatoma patients.